Training needs of extension specialists - Singh, Ajit; Saini, S.K. (2000)
This investigation was undertaken to determine the extension training needs of KVKs & extension scientists (ESs) of Punjab. It was conducted on 55 E.Ss and data were collected through mailed questionnaire by using a 3-point scale. The findings revealed that the area of Agricultural Development Agencies secured first rank as a whole. The data further showed that, in the area of Planning, "preparation of proforma for bench mark survey" secured first rank followed by "identifying needs and problems of the farmers" under the area of `Monitoring and Evaluation' the highest rank was earned by the items "Concepts and objectives of monitoring and evaluation". It is concluded that the training needs of the respondents, pertaining to all major areas, be met by imparting in-service or refresher training after every two years. - Reproduced
Keywords: Training